Investigation of the effects of Periplaneta americana (L.) extract on ischemic stroke based on combined multi-omics of gut microbiota - Yang, Xin; Hong, Canhui; Guan, Tangfei; Zhang, ChengGui; Xiao, Peiyun; Yang, Yongshou; Xiao, Huai; He, Zhengchun (Frontiers in Pharmacology, 2024)
Ischemic stroke (IS) is a highly lethal type of cardiovascular and cerebrovascular disease. Improving survival rates and promoting recovery in patients with IS pose significant challenges, however, recent research has identified the gut–brain axis as a therapeutic target. In this study, we evaluated the regulatory effect of Periplaneta americana (L.) extract (PAS840), which has established anti-inflammatory, antioxidant, and neuroprotective effects, on the gut microbiota using a rat model of temporary middle cerebral artery occlusion (tMCAO). We evaluated the protective effects of PAS840 on brain damage in IS rats through TTC (triphenyltetrazolium chloride), Nissl staining, and pathological section analysis. Additionally, we investigated the impact of PAS840 on the gut microbiota and metabolites using 16S rRNA sequencing, untargeted metabolomics of gut contents, and transcriptomics analyses of brain tissues to explore its mechanism of action. PAS840 intervention resulted in significant changes in the gut microbiota, including an increase in the abundance of probiotic flora, decrease in the abundance of harmful flora, and significant changes in metabolite profiles. It also attenuated brain damage, decreased platelet activity, inhibited oxidative stress and genes related to inflammation, and improved neurological function in rats. These findings suggest that PAS840 has preventive and therapeutic effects against IS via the gut–brain axis by regulating the gut microbiota and related metabolites. Accordingly, PAS840 is a candidate therapeutic drug for further research.